Quantitative analysis of 2, 3, 5, 4′-tetrahydroxystilbene-2-O-β-d-glycoside in wild Polygonum multiflorum and suspension cell cultures fed different precursors and elicitors. (March 2016) - Xia, Wanxia; Lei, Lei; Zhao, Wei; Feng, Yifan; Zhao, Shujin
Graphical abstract: Highlights: we established PM suspension cultures from calli. We investigated growth conditions and THSG yield of the suspension cultures. We assessed the genetic stability of the suspension cultures by flow cytometry. THSG content was measured in different parts of wild PM and cell cultures. The effects of precursors and elicitors on THSG content were investigated. Abstract: Polygonum multiflorum suspension cultures were established from calli and characterized during a culture period of 18 days. Flow cytometry analysis indicated a stable ploidy level in the cultured cells. THSG content was measured in different parts of wild PM and cell cultures after the addition of 4 precursors (jasmonic acid, methyl jasmonate, salicylic acid, and silver nitrate) and 4 elicitors (l -phenylalanine, glucose, sodium pyruvate, and sodium bicarbonate). PM vines, roots, calli, and suspension cultures had THSG contents of 24.125 ± 3.291, 42.751 ± 3.323, 0.022 ± 0.008, and 0.014 ± 0.003 mg/g (THSG content/dry weight, DW), respectively. THSG productivity was not significantly enhanced by the added elicitors or precursors.